World Economic Outlook, October 1985. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1985)
This report presents revised projections resulting from a country-by-country updating of the estimates published in the April 1985 World Economic Outlook. The projections are based on the usual technical assumptions of (1) unchanged nominal exchange rates among industrial countries; (2) unchanged oil prices in nominal U.S. dollar terms; and (3) 'constant policies.' The report also stresses the interactions of policies and developments among IMF members. These interactions are particularly evident from the way in which differences in economic policy mix have affected domestic savings and investment positions and hence interest rate differentials and trade flows.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet